Experimental and Numerical Study of Buckling Restrained Bracing Behavior with Combined Steel and Polyamide Sheath - Madjid Gholhaki (Iranian Society of Structrual Engineering (ISSE), 2019)
One of the most widely used system resisting against lateral loads in the design and retrofit of concrete and steel structures is steel bracing. One of the methods developed by the researchers is the use of confining members to prevent general buckling of bracing and reducing the effects of it. In this bracing system known as "Buckling Restrained Bracing, the axial load is born by bracing core and by using surrounding sheath, its overall buckling can be avoided. In this paper, experimental and numerical study of the effects caused by steel type of core of the distance of core from sheath on buckling restrained bracing was studied. Experimental models consist of six bracings with core of conventional ST37 and ST37-n steel (softened at a temperature of 1000 degrees by O'Neill method), in which the distance of core from sheath is zero, two, and three mm. Experimental results show that the use of softer steel with lower yield stress and with equal thickness in the core reduces bearing capacity and resistance or strength of bracing. However, bracing in smaller displacements started to energy waste. Increasing distance of the core from sheath also reduces bearing capacity and energy dissipation of bracing. In addition, increasing the distance of core from sheath to more than 2 mm causes the loss of symmetry and stability in hysteresis behavior of bracing and distortions resulting from local buckling in the bracing in pressure were intensified. Polyamide filler material had good resistance against pressure from the core and no certain damage was seen in it. Therefore, due to having less specific gravity, it could be a good alternative to concrete and reduce the overall weight of the bracing.